(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
By Law 10th december 2012, no. 219 and the subsequent Italian Legislative Decree 28th December 2013, no.154 was introduced the single state of filiation, with consequent unified treatment and not only equal protection – regardless of whether or not the birth took place within wedlock – and a full legal recognition of "natural" kinship. The accentuation of the principle of favor filii at both the regulatory and the jurisprudential levels, also with reference to the status of filiation, both at the time of its acquisition and at the time of its dispute, implies a redefinition of the institution of, which has now become detached from the logic of opposition (if not of reconciliation) between children born in and out of wedlock.